Roles of Dental Practitioners in Child Abuse and Neglect Responses: A Mixed-Methods Study in Aotearoa New Zealand - Han, Heuiwon (Auckland University of Technology, 2025)
The United Nations Convention on the Rights of the Child asserts that all children have the right to protection from abuse and exploitation. Child abuse and neglect (CAN) remain a serious and ongoing social issue in Aotearoa New Zealand with significant implications for the health, development, and wellbeing of children. Oral health practitioners (OHPs) are uniquely positioned to support child protection efforts due to their regular contact with children and families through the nation’s publicly funded dental care system for individuals under 18 years of age. Guided by a pragmatic paradigm and a commitment to finding practical solutions, this thesis aimed to explore how OHPs can be better supported to identify and respond to CAN concerns, and to develop evidence-based recommendations to strengthen their role in child protection. The research adopted an explanatory sequential mixed-methods design, implemented in four phases. First, a quantitative online survey assessed OHPs’ knowledge, attitudes, and perceived preparedness in responding to CAN. Second, a scoping review mapped international strategies aimed at enhancing the responsiveness of OHPs. Third, a review of legal and professional frameworks examined the regulatory requirements and ethical obligations surrounding CAN responses in Aotearoa New Zealand. Finally, qualitative interviews and focus groups explored the experiences and perspectives of OHPs, identifying barriers, enablers, and professional needs to enhance OHP responsiveness to CAN concerns. Findings indicate that while OHPs are not legally mandated to report suspected CAN, professional guidelines and legislation frameworks require them to engage in safeguarding practices to protect children. However, despite demonstrating empathy and a readiness to support affected families, OHPs’ practical engagement in child protection is hindered by limited capacities and support to respond to CAN concerns and participate in preventive strategies. Cultural misunderstandings, fears associated with the sensitive topic of CAN, and uncertainty about appropriate procedures were identified as key individual barriers. Systemic and organisational challenges, such as limited interdisciplinary collaboration, reduced trust in child protection agencies, and inadequate institutional support for OHPs, further hindered OHPs’ ability to respond safely and effectively. While these challenges were evident, the research also identified key strengths that OHPs bring to child protection efforts. Their ongoing relationships with children and families, clinical familiarity with orofacial manifestations of abuse, and trusted presence within community settings position them well to support prevention and early intervention approaches. Participants highly valued support through interdisciplinary collaborations and expressed a strong commitment to being part of collaborative practice. Participants emphasised the need for targeted training, culturally safe practice guidance, clearer legal and ethical frameworks, and stronger interdisciplinary collaboration to enhance their responsiveness and better support children and their families. This thesis highlights that OHPs have the potential to play a more meaningful and proactive role in child protection when supported through system-wide, culturally responsive, and strength-based approaches. The findings offer practical recommendations for educational providers, professional bodies, healthcare organisations, and policymakers to foster a more streamlined and effective child protection response. These efforts ultimately aim to advance equitable health and social outcomes for all children in Aotearoa New Zealand; a goal that reflects a shared vision and collective responsibility across sectors, communities, and society to ensure all children grow up safe, supported, and free from harm.